The influence of cavitation effects on the purification processes of beet sugar production juices - Zheplinska, Mariia; Mushtruk, Mikhailo; Vasyliv, Volodymyr; Sarana, Viktor; Gudzenko, Maxim; Slobodianiuk, Nataliia; Kuts, Anatoly; Tkachenko, Serhii; Mukoid, Roman (My University, 2021)
In the juices of sugar beet, the viscosity of the produced viscosity is determined. They contain sugars and non-sugary compounds. If they are in the form of associated or complex compounds, then when their state changes. Well under the action of external factors or at their removal from a solution it is obligatory. Its rheological properties will also change. Therefore, with the help of determining the viscosity, it is possible to conclude the complex processes that take place in juices under the action of the effects of vapor condensation cavitation, namely: the force between Leculiary bonds, the size of molecules, and the length of chemical bonds, etc. The paper presents studies of the influence of vapor-condensation cavitation effects on the change of such rheological properties of cell and diffusion juice as viscosity and surface tension. The viscosity of the steam treated juice is affected by complex transformational changes that occur with the associated compounds under the effects of vapor-condensation cavitation, which leads to their destruction and this leads to a decrease in their molecular weight and changes in concentration. Studies have shown that with increasing steam consumption for juice processing in the range of 0 – 1.5% by weight of juice the upper tension increases. Such legitimacy is also an indirect confirmation of the processes of destruction of the association. important compounds of diffusion juice under the influence of the effects of steam condensation cavitation.
Keywords: diffuse juice; surface tension; cavitation effects; associates; hydrodynamic cavitation; дифузний сік; соратники; кавітаційні ефекти; гідродинамічна кавітація; поверхневий натяг; кафедра біотехнології продуктів бродіння і виноробства